Pelatihan Pembuatan Vermikompos Sebagai Upaya Pemanfaatan Limbah dan Kemandirian Pengadaan Pupuk Organik di Desa Lelede Kecamatan Kediri Kabupaten Lombok Barat - Lorinanggarani, Ray Harmida; Apriani, Nita; Susilowati, Lolita Endang (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Lelede village is a village where many people make their living as livestock breeders. So a lot of livestock waste is not utilized and has an impact on the surrounding environment. This service activity aims to provide education and outreach as well as practice making vermicompost. The targets for implementing this service activity are farmer groups, women farmer groups and the Lelede Village community. This vermicompost is made with the help of earthworms (Eudrillus eugeniae). Making vermicompost using worms can reduce pollution from organic waste, one of which is animal waste. The more worms you add, the faster the process of decomposing organic material. The method used in this activity is counseling and training as well as conducting evaluations in the form of pretests and posttests with the result that 100% of participants understand the material provided and participants play an active role in the continuity of the program and are interested in carrying out training activities.